Editorial: 29th International conference on logic programming special issue – ADDENDUM. Issue 1 (10th August 2017) - LAMMA, EVELINA; SWIFT, TERRANCE
Abstract : The links to the online only Technical Communications in Lamma and Swift (2013) are unfortunately broken. All of the Technical Communications can be found here: https://www.cambridge.org/core/journals/theory-and-practice-of-logic-programming/article/editorial-29th-international-conference-on-logic-programming-special-issue/82FDD81073DC30A563ED242516CADAAE#fndtn-supplementary-materials